Odpowiedzi

Najlepsza Odpowiedź!
2010-01-25T16:30:00+01:00
8x+5=7x
8x-7x=-5
x=-5

7n+2=6n-3
7n-6n=-3-2
n=-5

-x+25=2x-2
-x-2x=-2-25
-3x=-27/(-3)
x=9

9z-7=-z-6
9z+z=-6+7
10z=-1/10
z=-1/10

25m-3=24m-4
25m-24m=-4+3
1m=-1
m=-1

-s+15=4s-14
-s-4s=-14-15
-5s=-29/(-5)
s=5,8

17y+18=19y+27
17y-19y=27-18
-2y=9/(-2)
y=4,5

8k-19=8k+19
8k-8k=19+19
0=38
4 4 4
2010-01-25T16:36:49+01:00
8x+5=7x
8x - 7x = -5
x=-5
8*-5 + 5= 7*-5
-35 = -35

7n+2=6n-3
7n-6n=-3-2
x = -5
-5*7 + 2= -5*6-3
-33 = -33

-x+25=2x-2
-x-2x = -2-25
-3x = -27 / -3
x= 9
-9+25 = 2*9-2
16=16

-9z-7=-z-6
-9z+z=-6+7
-8z= 1 / -8
z = - 1/8
4 7/8 = 4 7/8

25m-3=24m-4
25m-24m= -4+3
m=-1
-28 = -28

-s+15=4s-14
-s-4s= -14-15
-5s= -29 / -5
s= 5 4/5
9 1/5 = 9 1/5

17y+18=19y+27
17y-19y=27-18
-2y= 9 / -2
y= -4,5
-58,5 = -58,5

8k-19=8k+19
8k-8k = 19+19
0= 38


2 1 2
2010-01-25T16:54:08+01:00
8x+5=7x
8x-7x=-5
x=-5

7n+2=6n-3
7n-6n=-3-2
n=-5

-x+25=2x-2
-x-2x=-2-25
-3x=-27 / : (-3)
x=9

-9z-7=-z-6
-9z+z=-6+7
-8z=1/:8
z= -1/8

25m-3=24m-4
25m-24m=-4+3
m=1

-s+15=4s-14
-s-4s=14-15
-5s= -1/: (-5)
s=1/5

17y+18=19y+27
17y-19y=27-18
-2y=9/:(-2)
y= -4,5

8k-19=8k+19
8k-8k=19+19
0≠38
nie ma rozwiązania
2 5 2